Agreement study of keratometric values measured by Biograph/LENSTAR, auto‐kerato‐refractometer and Pentacam: Decision for IOL calculation. (September 2014) - Hashemi, Hassan; Asgari, Soheila; Miraftab, Mohammad; Emamian, Mohammad Hassan; Shariati, Mohammad; Fotouhi, Akbar
<x xml:space="preserve">Abstract</x> Background The aim was to determine the agreement in keratometric readings measured with the Biograph/LENSTAR, the Pentacam and an auto‐kerato‐refractometer in a 40‐ to 64‐year‐old population. Methods This report is part of the first phase of the population‐based Shahroud Cohort Eye Study. In virgin eyes, agreement among keratometry readings of three devices was examined in 7, 260 eyes using the Bland‐Altman method. The inter‐device 95 per cent limits of agreement (95% LoA) and 95% confidence interval for upper and lower limits of agreement were calculated. Comparisons were made for keratometric readings of the flat and steep meridians as maximum keratometry (max‐K), minimum keratometry (min‐K) and their average (mean‐K). Results Based on Biograph/LENSTAR measurements, averages of max‐K, min‐K and mean‐K were 44.70 ± 1.64, 43.87 ± 1.54 and 44.28 ± 1.58 D, respectively. The quantile‐quantile plot revealed that all three variables had normal distributions in this population. Agreement between the Biograph/LENSTAR and the auto‐kerato‐refractometer (max‐K difference: ‐0.03 D, 95% LoA: ‐0.81 to 0.75; min‐K difference: ‐0.08 D, 95% LoA: ‐0.85 to 0.68) was better than the agreement between the Biograph/LENSTAR and the Pentacam (max‐K difference: 0.50 D, 95% LoA: ‐3.24 to 4.25; min‐K difference: 0.59 D, 95% LoA: ‐3.00 to 4.17). The agreement between the Pentacam and the auto‐kerato‐refractometer (max‐K difference: 0.54 D, 95% LoA: ‐3.16 to 4.24; min‐K difference: 0.66 D, 95% LoA: ‐0.77 to 0.53) was worse than the other two pairs. Conclusion These three devices are not interchangeable in terms of keratometry for calculation of the intraocular lens power. Agreement between the Biograph/LENSTAR and the auto‐kerato‐refractometer can be increased with regression models but this is not true in case of Biograph/LENSTAR and Pentacam.